ANALISIS MANAJEMEN PEMBIAYAAN PENDIDIKAN MELALUI DIGITALISASI DALAM MENDUKUNG MUTU PENDIDIKAN - Mohammad Yogi Hamdi; Ari Lutfia Sari; Okke Rosmaladewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of educational financing through digitalization in supporting the quality of education at SDN 098 Ciroyom. The focus of the study includes the planning, implementation, supervision, and accountability of educational financing, as well as the contribution of digitalization in improving the quality of education. The study uses a qualitative approach with a case study research type. Data were obtained through observation, in-depth interviews, and documentation with informants consisting of the principal, the BOS treasurer, teachers, and the school committee. Data analysis was carried out using the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and drawing conclusions, while data validity was tested through source triangulation, technical triangulation, and member checking. The results of the study indicate that financing planning is carried out in a participatory manner through the preparation of the School Activity and Budget Plan (RKAS) by utilizing digital systems, such as the School Activity and Budget Plan Application (ARKAS), so that planning becomes more systematic, transparent, and in accordance with school needs. Financing implementation refers to the RKAS and technical instructions for the School Operational Assistance Fund (BOS), while supervision is carried out internally and externally to ensure accountability for budget use. Financial accountability is prepared transparently through fund utilization reports supported by comprehensive administrative evidence. The implementation of digitalization in financial management has been proven to improve financial management efficiency, strengthen transparency and accountability, and support the provision of infrastructure, improve teacher competency, and improve the quality of the learning process. Thus, the digitalization of education financial management has contributed positively to improving the quality of education at SDN 098 Ciroyom.